Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Kepuasan Pelanggan, Terhadap Loyalitas Pelanggan (Study pada Toko Pakaian Sinar Mulyo) - Desy Cahyaningrum; Arif Miftanudin; Johanis Souisa; Yuniarsih Ekawati; Badruddin (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This research aims to empirically test the influence of product quality, service quality, and customer satisfaction on customer loyalty. The problem faced by the Sinar Mulyo Tegowanu Grobogan clothing store is declining sales. The population in this study were all consumers at the Sinar Mulyo Clothing Store and the sample used in this study was 96 respondents. This research used purposive sampling technique and a questionnaire with a Likert scale. Then the data obtained was analyzed using SPSS 25 which includes validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing via t test and analysis of the coefficient of determination (R2). The results of this test show that product quality has no and no significant effect on customer loyalty. Based on the coefficient of determination value of 0.902, in this case it means that 90.2% of the variation in the customer loyalty variable is explained by the variables product quality, service quality and customer satisfaction. Meanwhile, the remaining 9.8% is explained by other variables outside the model.